The Observation at Mean Oedema Index Variations with Location and Histological subtypes in Supratentorial WHO G-I Meningiomas - Md Bashir Ahammed; Hafiz Asif Raihan; Nazmin Ahmed; Ruhul Kuddus Biplop; Md Moshiur Rahman; Hasnayen Faisal; Riad Habib; Firoj Ahmed Al-Amin; Md Motasimul Hasan; Bipin Chaurasia; Md Jalal Uddin Mohammad Rumi; Mashiur Rahman Majumder; et al. (Bangladesh Journal of Neurosurgery, 2024)
Background: The term meningioma is the noncommittal, all-encompassing name coined by Harvey Cushing for this tumor of meninges which is usually benign. The severity and variety of the peritumoral brain oedema may limit operative exposure and increase the difficulties of intraoperative procedures; however, its pathogenesis is not clearly documented. Several factors, such as tumor size, location and histology, mechanical compression of draining vein by the tumor have been proposed as mechanism of peritumoral brain oedema Aims: The objective of this study was to determination of mean oedema index in different locations and histological subtypes in patients with supratentorial WHO GI meningiomas Methods: The study was conducted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from September, 2016 to March, 2018. This study was a cross sectional study. Data collection sheets were used to collect necessary information. Total 75 cases were selected consistent with inclusion and exclusion criteria. Tumor volume and localization and the presence of peritumoral brain oedema (PTBOe) were determined by MRI (Magnetic Resonance Image). All patients underwent microsurgical removal of tumor. Surgically resected meningiomas were classified histopathologically based on criteria of the new World Health Organization (WHO) classification. Regarding location and histological subtypes of tumor the study population were divided into 6 groups and 8 groups respectively.Statistical analyses were done by Statistical Packages for Social Sciences (SPSS-v.25). Results: A total 75 cases were selected consistent with inclusion and exclusion criteria from September, 2016 to March, 2018. Regarding location; the mean oedema index for each of the six groups was calculated and recorded. The F value was 5.97 and the P-value was 0.0001 which was less than 0.05. This result signifies that there was association between perilesional oedema in supratentorial meningioma to its location. So, Mean Oedema Index in Intracranial Supratentorial Meningiomas vary with its location. On the other hand, regarding histopathological subtypes, meningiomaswere divided into eight groups-the mean oedema index of each of the eight groups was calculated and recorded. The F value was 1.62 and P-value was 0.145 which was more than 0.05. This result signifies that there was no association between perilesional oedema in supratentorial meningioma to its histological subtypes. So mean oedema index in intracranial supratentorial meningiomas does not vary with its histological subtypes. Conclusion: Mean Oedema Index in Intracranial Supratentorial Meningiomas vary with its location but does not vary with histological subtypes Bang. J Neurosurgery 2023; 13(1): 10-13